Development disparities in Northeast India - Bhattacharya, Rakhee; Maulana Abul Kalam Azad Institute of Asian Studies (Kolkata, India) (New Delhi : Foundation Books, 2011)
India's recent reform measures have transformed the socioeconomic landscape of many states; however, it has left a few others behind. Development Disparities in Northeast India attempts to determine Northeast India 's place in the country's economic growth map. It examines whether India's liberalization has infused any hope into the Northeastern states of India. This book objectively analyses Northeast India's intra-regional variations and relates these to a pan-regional analytic grid thereby connecting it to the rest of India. The book opens a debate by examining critical issues like the colossal gap between supply steered policies of the central government and demands of the people in this region. It also addresses the issues of rampant corruption, dismal failure of governance and an insurgent economy that drives a sinister parallel economy within the region. This book will be of interest to graduate students, researchers, academicians and policymakers.
Title from publisher's bibliographic system (viewed on 02 Oct 2015).
Keywords: Economic development -- India, Northeastern; Economic development -- India, Northeastern -- Statistics; India, Northeastern -- Economic policy; India, Northeastern -- Economic policy -- Statistics; India, Northeastern -- Economic conditions; India, Northeastern -- Economic conditions -- Statistics